A new species of Aphanoblastella Kritsky, Mendoza-Franco and Scholz, 2000 (Monogenea, Dactylogyridae) parasitic on heptapterid catfish (Siluriformes) in the Neotropical region - Yamada, Fabio H.; Acosta, Aline A. [UNESP]; Yamada, Priscilla De O. F. [UNESP]; Scholz, Tomáš; Da Silva, Reinaldo J. [UNESP] (Springer Nature, 2018)
Aphanoblastella magna n. sp. is described from the gills of the heptapterid catfish Pimelodella avanhandavae Eigenmann, 1917 in southeastern Brazil (Paraná River Basin). This new species most closely resembles Aphanoblastella chagresii Mendoza-Franco, Aguirre-Macedo and Vidal-Martínez, 2007 described from a congeneric fish host in Panama, but can be distinguished by the shape of the accessory piece and shape and size of the ventral and dorsal bars. From the other species of the genus, A. magna n. sp. differs mainly in the shape of the male copulatory organ (MCO), which is sinuous, versus spirally coiled in other species of the genus, except for A. travassosi (Price, 1938), and by the accessory piece which resembles a 'shoehorn'. Aphanoblastella magna n. sp. is the seventh species of the genus and the first dactylogyrid described from P. avanhandavae. A partial 28S rDNA gene sequence of the new species is also provided; it forms a monophyletic clade with two congeners for which molecular data are available.
Keywords: 28S rDNA; Ancyrocephalinae; catfish; freshwater fish; Neotropical region; Paraná River basin